Development of the agro-industrial complex as an incentive for economic growth of the country (on the example of the North Caucasus Federal District and the Republic of North Ossetia – Alania) - A. I. Naniev; M. V. Volik (Вестник университета)
In modern economic conditions, there are a number of problems with Russia's economic growth. To stabilize it and increase its level, it is advisable to develop different sectors of the economy. One of the promising areas is the development of agriculture, agro-industrial complex. This paper studies the current state of the agro-industrial complex in the North Caucasus Federal District and the Republic of North Ossetia - Alania. The analysis of the current state of the agro-industrial complex of the North Caucasus Federal District showed that all the regions that are part of it have territorial and climatic opportunities for the development of the studied economic sector. The analysis of the state of the agro-industrial complex of the Republic of North Ossetia - Alania allows us to conclude that the region occupies a leading position in the production, processing and sale of products of the agro-industrial sector. Further stabilization and development of the agro-industrial complex in the region will have a significant positive impact on the country's economic growth.